Early Detection of Postpartum Blues with a Technological Approach Method - Novalia Widiya Ningrum; Muhammad Zulfadhilah (PT.Mantaya Idea Batara, 2025)
Background: Baby blues, also referred to as postpartum blues or postpartum distress syndrome, is an emotional state experienced by mothers following the birth of their first child. This condition can adversely affect both the mother and the infant. Multiple factors, such as insufficient family support, are believed to contribute to the rising incidence of baby blues. Given the prevalence of these cases, disseminating information through expert systems is essential. The Certainty Factor (CF) method is commonly employed in expert systems to address the uncertainty inherent in expert assessments. This study seeks to facilitate early diagnosis of psychological disorders in postpartum mothers by calculating a weighted symptom score, which produces a CF score to guide diagnosis and intervention. Data were collected through interviews, observations, and a review of relevant literature on postpartum blues. The research methodology follows the waterfall model, encompassing needs analysis, system design, system implementation, and system testing. The expert system application utilizes the Certainty Factor method. This system is anticipated to support the community by enabling early detection of psychological disorders in postpartum mothers.